SOSIALISASI KEBENCANAAN SEBAGAI UPAYA PENINGKATAN PENGETAHUAN DASAR SISWA TERHADAP MITIGASI BENCANA - Ruman, Rifyan; Nanlohy, Willem Dominggus; Hanafi, Nurul Salsabila; Patty, Farhani Amalia; Talaohu, Junior; Ramadhan, Risky (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Indonesia is a country that has a high level of vulnerability to natural disasters. Based on the disaster risk index, the Maluku Islands have a fairly high level of tsunami disaster potential. Small islands are often places that are vulnerable to tsunami disasters. Therefore, community preparedness on small islands is very important in facing this potential disaster. The aim of this outreach is to provide knowledge about disaster preparedness from an early age. This activity is a form of community service through outreach. The results of this outreach activity teach students to anticipate disasters, act when a disaster occurs, and handle disasters. Children are classified as vulnerable to disaster management efforts and therefore require special efforts to improve basic knowledge about disasters.